(untitled) (Economics and region, 2021)
The article analyzes the organic market of Ukraine and in accordance with the world experience according to scientific approaches. Four main stages of formation and development of the market of organic goods are identified. Currently, Ukraine ranks 11th among countries in terms of land area of organic specialization. But only 1% (381 thousand hectares) of the total area of agricultural land is used for growing organic matter in Ukraine. The leader among European countries is Spain, which uses 1.97 million hectares of land for growing organic products. The state promotes the development and regulates the activities of producers of organic goods through laws and regulations. In addition, the most common basic regulatory standards and rules in force in the European Union are identified, equivalent to EU standards, in third countries, in particular Ukraine. Today, 18 certification bodies from Switzerland, France, Austria, the Netherlands, Turkey, Germany and Italy operate in Ukraine, including the Ukrainian certification body Organic Standard. The most common are: National Organic Program of the US Department of Agriculture (American USDA National Organic Program – NOP); Japanese Law on Standardization and Proper Labeling of Agricultural and Forestry Products with Relevant Guidelines for Organic Production (Japanese Agricultural Standard – JAS); Swiss organic rules (Swiss Organic Regulation). Public authorities in developed countries actively support organic production, as it helps to strengthen the domestic market, increase exports and help solve economic and environmental problems. Today, 32 countries have fully approved standards for organic products, 9 countries are implementing standardization, 15 countries – the development of such standards. But world experience shows that the state supports a project only when it begins to bring money and becomes part of the economy. Based on foreign experience, appropriate measures have been proposed to support domestic organic producers.